A Calibrated Charge Pump for Mismatch Reduction in PLL - Hao Liu; Zixuan Wang; Chuang Li; Jianhui Wu (Institute of Advanced Engineering and Science, 2012)
An improved charge pump (CP) for phase locked loop (PLL) applications is presented. The proposed charge pump circuitry employs a variable current source in its sink path, which realizes feedback network for calibration. This scheme of charge pump minimizes mismatch between the sourcing current and the sinking current efficiently. The circuit is simulated in 0.18um CMOS technology and the simulation results show that good current matching characteristics can be achieved. The mismatch between the sourcing current and the sinking current can be reduced to less than 0.01% and the range of charge pump output voltage varies from 0.3V to 1.5V.